Monitoring pulmonary VO2 on-kinetics during a 3-year period in youth elite-cyclists - Hovorka, M.; Prinz, B.; Zöger, M.; Rumpl, C.; Nimmerichter, A. (Journal of Science and Cycling, 2021)
Pulmonary oxygen uptake on-kinetics provide insights into the processes underlying the increase in O2flux from ambient air to muscle mitochondria following the onset of exercise. It is well known that aging from childhood to adulthood has a detrimental effect on the oxygen uptakeon-kineticresponse. Therefore, the aim of this study was to investigate the effects of aging on pulmonaryoxygen uptakeon-kinetics in nine youth elite-cyclists throughout a period of ~3 years. Participants visited the laboratory twice on three occasions within ~3 years. Anthropometric measures, a graded ramp-exercise test and two square-wave transitions frombaseline to a constant work-rate within the moderate and heavy intensity exercise domain, respectively were conductedduring these visits.The parameter estimates of the oxygen uptake on-kinetic response were resolved by least-squares non-linear regression.A repeated measures ANOVA was used for statistical analyses and the level of statistical significance was set at P< 0.05. During moderate and heavy intensity exercise, the time constant and the amplitude of the primary phase improved overtime (P < 0.01). However, the slow componentevident during heavy intensity exercisewas not significantly affected by time (P > 0.05). These results suggest that regularly performed endurance training of elite youth-cyclists augments the potential for oxidative phosphorylation and reduces the impairmentsnormallyobserved with aging.